Structural design optimization of CFRP/Al hybrid co‐cured high‐speed flywheel with the particle swarm optimization algorithm. Issue 4 (9th January 2023) - Zhong, Bingfu; Li, Junli; Cai, Xiaojiang; Chen, Tao; An, Qinglong; Chen, Ming
Abstract: With the development of CFRP materials and co‐cured structure, CFRP/Al hybrid co‐cured materials have been widely used for high‐speed energy storage flywheels. Therefore, it has become a hot research topic, which is to design a CFRP/Al hybrid co‐cured flywheel with a reasonable structure. In this paper, a particle swarm optimization algorithm is presented for improving the energy storage density to optimize the structure of the CFRP/Al hybrid co‐cured high‐speed flywheel. First, the stress and structural analysis of the flywheel are carried out based on energy storage. The inner‐radius‐to‐outer‐radius λ and the radial wall thickness h are chosen as the objective function because the λ and h are the factors which influence the energy storage density of the flywheel. Based the Tsai‐Hill criterion, the assembly interference t is the constraint condition which is the factor to meet the stress of design requirements. Then, the mathematical model of the flywheel is established by the objective function and the restriction with the particle swarm optimization algorithm (PSO). Finally, a specific CFRP/Al hybrid co‐cured flywheel is presented for the structural optimization with PSO by improving the energy storage density. In addition, the optimized flywheel is carried out to examine the static and dynamic requirements by the finite element method. The results indicate the PSO can be effectively used to optimize the structure of the CFRP/Al hybrid co‐cured high‐speed flywheel. Abstract : Schematic diagram of MA mechanisms of structural design optimization.